Faktor-Faktor Yang Berhubungan Dengan Kepatuhan Pengobatan Pada Pasien Tuberkulosis Di UPT Puskesmas Kepanjen Kabupaten Malang - Hilda Tampubolon; Endang Sri Redjeki; Suci Puspita Ratih (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Tuberculosis (TB) is an infectious disease that causes the most common death from a single infectious pathogen, and is among the 20 leading causes of death worldwide. Treatment is one of the important efforts to control TB, and compliance with treatment is very necessary to achieve recovery. This research was conducted to identify whether the variables age, education, knowledge, and the role of the Drug Swallowing Supervisor (PMO) have a relationship with TB treatment compliance. This research uses an analytical cross-sectional approach. The sample in this study was 32 SO TB patients who were undergoing treatment at the Kepanjen Community Health Center, Malang Regency. The results of the analysis using the alternative Chi-square test, namely the Kolmogorov-Smirnov Z test and Fisher's exact test, show that the variables are age (P value 0.690), level of education (P value 0.675), level of knowledge (P value 0.573), and The role of the PMO (P value 0.224) does not have a significant relationship with the level of TB treatment compliance in patients seeking treatment at the Kepanjen Community Health Center.